ANTIBACTERIAL RESISTANCE PATTERN OF PSEUDOMONAS AERUGINOSA ISOLATED FROM CLINICAL SAMPLES AT A GENERAL HOSPITAL IN PADANG, WEST SUMATRA, INDONESIA - Rustini, Rustini; Jamsari, Jamsari; Marlina, Marlina; Zubir, Nasrul; Yuliandra, Yori (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objectives: Pseudomonas aeruginosa is an opportunistic pathogen that has an innate resistance to some antibiotics. This bacterium is one of the mostcommon causes of nosocomial infections that include surgical wound infections, burns, and urinary tract infections. The bacteria have been reportedlyresistant to many antibiotics and have developed multidrug resistance (MDR). The objective of the study was to determine the resistance pattern ofP. aeruginosa isolated from clinical samples of patients against some major antibiotics. Methods: Isolates of P. aeruginosa were obtained from clinical sample of urine, sputum, swabs, pus, feces, and blood and cultured in cetrimide agar. P.aeruginosa ATCC 27853 was used as a positive control. The antibacterial susceptibility testing was conducted against 13 antibiotics: Ceftazidime, cefotaxime,ceftriaxone, cefoperazone, ciprofloxacin, levofloxacin, ofloxacin, gentamicin, amikacin, piperacillin, ticarcillin, meropenem, and imipenem. The examinationwas carried out using agar diffusion method of Kirby-Bauer and following the standards from Clinical and Laboratory Standards Institute (CLSI). Results: The results showed that bacterial resistance was established against all tested antibiotics. The highest number of resistance was shownagainst ceftriaxone (44.21%), whereas the most susceptibility was exhibited against amikacin (only 9.47% of resistance). MDR P. aeruginosa (MDRPA)was detected on almost all clinical samples tested, except the feces. The sample with the highest percentage of MDRPA was the pus. Conclusion: The study concludes that the most effective antibiotic against P. aeruginosa is amikacin (91.51%), whereas the most resistance is exhibited to ceftriaxone (43.16%).